2011
DOI: 10.5781/kwjs.2011.29.6.676
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Welding Parameters on Macrostructure and Mechanical Properties of Friction-Stir-Spot-Welded 5454-O Aluminum Alloy Sheets

Abstract: Friction stir spot welding between 5454 aluminum alloy sheets with the different thicknesses of 1.4 and 1.0 mm was performed. In the welding process, the tool for welding was rotated ranging from 500 to 2500, and plunged to the depth of 1.8 mm under a constant tool plunge speed of 100 mm/min. And then, the rotating tool was maintained at the plunge depth during the dwell time ranging from 0 to 7 sec. The pull-out speed of the rotating tool was 100 mm/min. The increase of tool rotation speed resulted in the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Choi et al [353] studied spot FSWed joints of sheets made of 5454 alloy (Table 4) with the different thicknesses of 1.4 and 1.0 mm obtained under the TRS in the range from 500 to 2500 rpm, and plunging to the depth of 1.8 mm under a constant tool plunge speed of 100 mm/min. The rotating tool was maintained at the plunge depth during the dwell time ranging from 0 to 7 sec.…”
Section: Tool Rotation and Welding Speedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Choi et al [353] studied spot FSWed joints of sheets made of 5454 alloy (Table 4) with the different thicknesses of 1.4 and 1.0 mm obtained under the TRS in the range from 500 to 2500 rpm, and plunging to the depth of 1.8 mm under a constant tool plunge speed of 100 mm/min. The rotating tool was maintained at the plunge depth during the dwell time ranging from 0 to 7 sec.…”
Section: Tool Rotation and Welding Speedsmentioning
confidence: 99%
“…Studying spot FSWed joints of sheets made of 5454 alloys Choi et al [353] found that the enhancement of tool rotation speed changed the macrostructure of the friction-stir-spot-welded zone, especially the geometry of the welding interface. However, the change in the dwell time at the plunge depth of the tool only slightly affected the microstructure of the welds.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the spot FSW joints of sheets made of 5454 alloys, Choi et al [417] found that the enhancement of tool rotation speed changed the macrostructure of the friction-stirspot-welded zone, especially the geometry of the welding interface. However, the change in the dwell time at the plunge depth of the tool only slightly affected the microstructure of the welds.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…Choi et al [417] studied the spot FSW joints of sheets made of the 5454 alloy (Table 6) with different thicknesses of 1.4 and 1.0 mm obtained under a TRS ranging from 500 to 2500 rpm and a plunging depth of 1.8 mm with a constant tool plunge speed of 100 mm/min. The rotating tool was maintained at the plunge depth during the dwell time ranging from 0 to 7 s. The pull-out speed of the rotating tool was 100 mm/min.…”
mentioning
confidence: 99%